2006
DOI: 10.1590/s0100-204x2006000700003
|View full text |Cite
|
Sign up to set email alerts
|

Produção e qualidade do grão do arroz irrigado infestado por adultos de percevejo-das-panículas

Abstract: Resumo -O objetivo deste trabalho foi comparar os danos qualitativos e quantitativos, causados por adultos de Oebalus poecilus (Dallas) Stal, em panículas de 39 genótipos de arroz irrigado. Em campo, as panículas emergentes foram isoladas em gaiolas e infestadas com dois insetos, no início da fase leitosa das espiguetas. Panículas não infestadas serviram de testemunha. Após a colheita, amostras compostas de 50 espiguetas de cada grau de infestação, para cada genótipo, foram semeadas em telado, e a emergência f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…There was observed a reduction of 32.7% in the weight of the two-insect infested panicle, a value greater than that recorded by Ferreira & Barrigossi (2006), 27.7%, when they evaluated 20 genotypes of irrigated rice also infested with two O. poecilus adults. The authors exposed the panicles at R5-R9 stage to the insects, whereas in this work this only occurred in the most susceptible stage of the spikelets (R5) (Krinski & Foerster, 2017), thus the damage caused by the bug feeding on IRGA 424 RI was more pronounced, indicating that this cultivar is more susceptible to the attack of these insects than the genotypes evaluated by the authors.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…There was observed a reduction of 32.7% in the weight of the two-insect infested panicle, a value greater than that recorded by Ferreira & Barrigossi (2006), 27.7%, when they evaluated 20 genotypes of irrigated rice also infested with two O. poecilus adults. The authors exposed the panicles at R5-R9 stage to the insects, whereas in this work this only occurred in the most susceptible stage of the spikelets (R5) (Krinski & Foerster, 2017), thus the damage caused by the bug feeding on IRGA 424 RI was more pronounced, indicating that this cultivar is more susceptible to the attack of these insects than the genotypes evaluated by the authors.…”
Section: Resultsmentioning
confidence: 63%
“…Abiotic factors such as temperature and relative humidity of the air and biotic factors, such as the presence of natural enemies and the susceptibility of cultivars may also affect the damage intensity (Barrigossi, 2008;SOSBAI, 2016). Several studies have demonstrated differences among genotypes of rice in relation to total spikelet loss (qualitative and quantitative) due to attack of bugs, however, they were carried out using cultivars adapted to the Central-West region or even to an upland rice system (Silva et al, 2018;Ferreira & Barrigossi, 2006;Krinski & Foerster, 2017). Rev.…”
Section: Introductionmentioning
confidence: 99%
“…: Noctuidae), a polyphagous insect that causes great damage to rice crops (Ferreira and Barrigossi, 2004). There were also registers of Eulophidae individuals parasitizing Odonata eggs (Fursov and Kostyukov, 1987), a group frequently found in this system, favored by areas that stay flooded for a long period throughout the year.…”
Section: Discussionmentioning
confidence: 96%
“…This process facilitates the entry of fungi from the genus Bipolaris Shoemaker, Fusarium Link, Neovossia Körnicke, Alternaria Nees, Curvularia Boedijn, and Nigrospora Zimmerman, among others [5], causing the symptomatology known as "grain staining." Therefore, the established relation between infestations is greater than 0.7 insects/panicle of O. insularis, and the infection rate recorded in the "milky" grain phase affects the crop yield [6], [7].…”
Section: Introductionmentioning
confidence: 99%